The cultural component and its relationship to the formation of mental illness - MEGUELATI, Sami; BECHKA, Azzeddine (Journal of Human Sciences, 2020)
Man is born in an environment, refined by its features, and his character is imprinted with what culture holds, where the direction of the normality that each member seeks is related to several variables, beginning with the mechanisms of adapting to the data of the situation during the experiences of daily life. The inclusion of the cultural dimension in the literature of international institutions has been gradual and differentiated, similar to (APA), through successive versions, as it became clear in the fifth edition the importance of the cultural component, which not only expands in its formative content but also in the influence of the cultural context and its multiple interactions in the formation of mental illness, as well as It is with women as a gender. This paper examined the importance of the cultural component and the necessity of including it in the publications of (DSM) during diagnosis, starting with a psycho-social pathology model such as anxiety.